Serum Neurofilament Light Predicts 6-Month Mental Health Outcomes in a Cohort of Patients With Acute Ischemic Stroke - Wang, Duo-Zi; Guo, Fu-Qiang; Guo, Lei; Yang, Shu; Yu, Neng-Wei; Wang, Jian; Wang, Jian-Hong (Frontiers in Psychiatry, 2022)
Background Mental health problems after acute ischemic stroke (AIS) have caused wide public concerns, and the study on early identification of these disorders is still an open issue. This study aims to investigate the predictive effect of circulating neurofilament light (NfL) on long-term mental health status of AIS patients. Methods This study collected demographic information and mental health measurements from 304 AIS patients from May 1, 2016 to Dec 31, 2019. Baseline serum neurofilament light (NfL) was determined within 2 hours since patient admission. Six months after AIS onset, the degree of symptoms of depression, anxiety, and insomnia was assessed by the Chinese versions of the 9-item Patient Health Questionnaire (PHQ-9), the 7-item Generalized Anxiety Disorder scale (GAD-7), the 7-item Insomnia Severity Index (ISI) respectively. Subjects were divided into the high NfL group and the low NfL group. Multivariate logistic regression analysis was performed to identify factors associated with these mental health problems. Results The high NfL group had significantly higher PHQ-9, GAD-7 and ISI scores than the low NfL group. The prediction of serum NfL for major depression generated a sensitivity of 70.27%, a specificity of 67.79% and an AUC of 0.694. The prediction of serum NfL for anxiety generated a sensitivity of 69.23%, a specificity of 64.02%, and an AUC of 0.683. The prediction of serum NfL for insomnia generated a sensitivity of 75.00%, a specificity of 66.43% and an AUC of 0.723. Higher serum NfL was a risk factor of post-AIS depression [ORs (95% CI): 4.427 (1.918, 10.217)], anxiety [ORs (95% CI): 3.063 (1.939, 6.692)] and insomnia [ORs (95% CI): 4.200 (1.526, 11.562)]. Conclusions These findings imply that circulating NfL might be a potential biomarker of long-term mental health problems after AIS.